Scrotal Verrucous Carcinoma: An Exceptional Localization of a Rare Tumor - K. Imrani; A. Lahfidi; L. Belkouchi; H. Jerguigue; R. Latib; Y. Omor (Case Reports in Medicine)
Scrotal verrucous carcinoma is a rare entity. It is rarely metastatic especially in lymph nodes. Imaging is important for local extension in order to guide the surgical procedure. The diagnostic is histological. The treatment is based on surgical excision. The prognosis is relatively good, but local recurrences are frequent. We report a case of scrotal verrucous carcinoma in a 49-year-old man evolving for 1 year.